Analisis Beban Kerja Mental Pegawai PKBM Mutiara Menggunakan Metode Nasa Task Load Index - Beta Arya Ash Shidik Arya; Yohandika Tri Apriliyanto (Fakultas Teknik dan Rekayasa, 2024)
PKBM Mutiara is a non-formal education institution in Pemalang district which was founded in 2007. Currently PKBM Mutiara has 15 employees who have different duties and responsibilities. The chairman of PKBM stated that recently there had been complaints of work fatigue from several employees. Therefore, PKBM Mutiara wants to know the workload borne by each employee. The workload analysis method used is the NASA TLX method (National Aeronautics and Space Administration Task Load Index). Employees will assess their workload conditions based on 6 dimensional measurement factors, namely Mental Needs (KM), Time Needs (KW), Physical Needs (KF), Effort (U), Work Performance (PK), and Frustration Level (TF). Based on the calculation of employee workload scores at PKBM Mutiara, It is known that there are 2 employees whose workload is in the